Chinese onion (Allium chinense), an evergreen vegetable: A brief review - Shahrajabian, Mohamad Hesam; Sun, Wenli; Cheng, Qi (Polish Journal of Agronomy, 2020)
The history of using medicinal herbs and plant dates back to the ancient times. Chinese onion (Allium chinense) is famous as a plant for both food and medicinal purposes. It is widely cultivated as a vegetable and native to China. Its bulbs are commonly processed into pickles and spices. The bulb is anthelmintic, anti-inflammatory, antiseptic, antispasmodic, carminative, diuretic, expectorant, febrifuge, hypoglycaemic, hyptensive, lithontripic, stomachic and tonic. It can be also used to prevent oral infection and tooth decay. The most important chemical constituents of the essential oil derived from Allium chinense are: dimethyl disulfide, diallyl sulfide, allyl isothiocyanate, methyl allyl disulfide, methyl propyl disulfide, α-pinene, dimethyl trisulfide, β-pinene, 1,3-dithiane, limonene, diallyl disulfide, linalool, methyl allyl trisulfide, methyl propyl trisulfide, dimethyl tetrasulfide, diallyl trisulfide, diallyl thiosulfinate, and allyl methyl tetrasulfide.